Evaluation of Stainless Steel Fasteners for Bolted Field Splice Connections of ASTM A1010 Corrosion-Resistant Steel Plate Girders. Issue 1 (2017) - Williams, Thomas R.; Xia, Xuemeng; Darby, Thomas E.; Sharp, Stephen R.
The Virginia Department of Transportation, Richmond, initiated this study to compare the mechanical properties, availability, and costs of stainless steel fastener materials for use with ASTM A1010 stainless steel plate. The investigation focused on fastener materials included in ASTM A193 and compared them with ASTM A325 bolts. The ASTM A193 bolts tested were the B6, B8, and B8M. Test results indicated that the ASTM A193 B8 fasteners provided the most economic combination of mechanical strength, corrosion resistance, and cost. Uniaxial tension tests and Skidmore–Wilhelm rotational capacity tests revealed that the B6 fasteners had high strength but lower ductility, whereas the B8M fasteners had lower strength but higher ductility. The B8 fastener had an ideal combination of strength and ductility. The mechanical performance of the ASTM A193 fasteners was improved further by the use of hardened washers. Because the bolts are hot forged, sensitization, which can reduce corrosion resistance, was of concern. Standard testing indicated that the B8 and B8M as-received bolts were unsensitized. The cost of the B8 fasteners compared favorably with that of other stainless steel fasteners. Further, the B8 fasteners are available from manufacturers that comply with Buy America requirements. The cost of stainless steel fasteners is higher than that of ASTM A325 steel fasteners. As their use increases, however, larger orders may help reduce prices. The initial research indicates that stainless fasteners could be a structurally sound option to use to build reduced maintenance bridges.